Constraining the history of water and climate on Mars through light element stable isotope analysis of volatiles in returned martian samples - Monica M. Grady (Proceedings of the National Academy of Sciences, 2025)
Much has been learned about Mars through data returned from space missions and analyses of martian meteorites. There are, however, many questions still outstanding which cannot currently be answered—including the issue of whether there is, or was, life on Mars. The return of a cache of samples—including of the atmosphere—from separate locations in Jezero Crater and with differing petrogeneses will provide the international community with the opportunity to explore part of the evolutionary history of Mars in great detail. Specifically, measurements of the isotopic compositions of the light elements H, C, N, O, Cl, and S can be used to follow how volatile species cycle through the different martian volatile reservoirs (atmosphere, lithosphere, cryosphere, and hydrosphere). Measurement of isotopic fractionation enables inference of the environmental conditions (e.g., temperature, water/rock ratio) under which fractionation occurred. Knowing the contextual relationship of the materials to their geological settings, coupled with precise compositional measurements will enable a more thorough understanding of martian volatile history and allow a picture to be constructed of water and climate on Mars as represented at Jezero Crater.